2009
DOI: 10.4081/ijas.2009.s2.111
|View full text |Cite
|
Sign up to set email alerts
|

Study of β-defensin polymorphisms in Valle del Belice dairy sheep

Abstract: The aim of this work was to sequence the exons of β-defensin 1 and 2 genes (SBD1 and SBD2) in Valle del Belice dairy sheep in order to identify polymorphisms. The study was conducted on 60 samples from three flocks. Six SNPs were identified: two in SBD1 and four in SBD2. Both genes consist of two exons and one intron. In SBD1 gene, SNPs were found only in the exon 2, whereas in SBD2, SNPs were detected in both exons. In both genes, SNPs were located in the coding regions and in the 3'-UTR. The SNP in SBD2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…No studies have been found that evaluate polymorphisms in the GBD‐1 gene in goats. In sheep, a closer species, Monteleone et al described two SNPs in the β‐defensin 1 gene: at position 1747 of exon 2 and at position 1757 of terminal region 3′. Transitions were A to G and T to C types, respectively.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…No studies have been found that evaluate polymorphisms in the GBD‐1 gene in goats. In sheep, a closer species, Monteleone et al described two SNPs in the β‐defensin 1 gene: at position 1747 of exon 2 and at position 1757 of terminal region 3′. Transitions were A to G and T to C types, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Transitions were A to G and T to C types, respectively. The GBD‐1 gene has been the most polymorphic gene, compared to sheep β‐defensin 1 gene ( SBD‐1 ), as described by Monteleone et al, and to sheep β‐defensin 2 gene ( SBD‐2 ), described by the same authors and Souza et al when analysing a sheep herd from Amazon.…”
Section: Discussionmentioning
confidence: 94%
“…Polymerase chain reaction (PCR) was performed on DNA samples to isolate and amplify a fragment length of 392 bp, comprising the exon II and part of the 3'-UTR of SBD-2. Primers used for PCR were those described by Monteleone et al (2009) Amplifications were carried out in a final volume of 25 µL, containing 1X STR 10X buffer; 3 mM MgCl2; 1.2 mM of each dNTP; 5 pmol primer; 1 U Taq DNA polymerase (500 units, Invitrogen, Life Technology, Carlsbad, CA, USA); and 50-100 ng genomic DNA. The initial desnaturation temperature was 94°C for 5 min, followed by 30 cycles of 94°C for 1 min, 60°C for 45 s, and 72°C for 1 min.…”
Section: Sample and Laboratory Proceedingsmentioning
confidence: 99%
“…In a study evaluating polymorphisms in SBD-2 in Italian sheep, four SNPs were found: one in exon I, and three in exon II (Monteleone et al, 2009). Monteleone et al (2011) conducted a study of Italian sheep and found five SNPs: one in exon I; and four in exon II, some of which were found to cause changes in the SBD-2 amino acid chain.…”
Section: Introductionmentioning
confidence: 99%
“…SBD-2 contains a total of 64 amino acids. Monteleone et al (2010Monteleone et al ( , 2011 discovered an SNP in the 1659th position of the gene (G to A), which substitutes the 42nd amino-acid arginine for lysine.…”
Section: Introductionmentioning
confidence: 99%